IMPLEMENTATION OF INCLUSIVE VILLAGE POLICY IN BIRA TENGAH VILLAGE, SOKOBANAH DISTRICT - Juliyandari, Mustaqima; Sri Rahayuningsih, Eni (JURNAL EKBIS, 2024)
This study aims to examine the implementation of inclusive village policies in Bira Tengah Village, Sokobanah District. The research method used is qualitative with a phenomenological approach. Data collection techniques are carried out by means of observation, interviews and documentation. The findings show that Bira Tengah Village has taken various significant steps to achieve inclusiveness, the village government is trying for all levels of society to participate in the development process in order to maintain the value of equality in the social realm, this can be seen from the inclusion of all levels of society in the preparation of village programs, infrastructure improvements, and increasing access to health services. However, although most of the Inclusive Village policies have been implemented, there are still obstacles in terms of socialization and regulation of the Law from the local government regarding the Inclusive Village Policy, this has caused several programs to not run optimally.